Analisis Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembeli Produk Melalui Kepuasan Konsumen Kosmetik Wardah di Kota Makassar - Fildzah Multarahmi; Novita Rosanti; Rachman Suwandaru; Karta Negara Salam (Movere Journal, 2025)
The purpose of this study was to determine the influence of product quality and price on purchasing decisions through consumer satisfaction of Wardah cosmetics in Makassar City. The sample in this study was part of all Wardah consumers in Makassar City who were currently using Wardah products with a total of 100 respondents. The analysis method used in this study used Smart PLS, Descriptive Analysis Testing and Hypothesis Testing. The results of this study indicate that (1) Product quality has a positive and significant effect on consumer satisfaction (2) Price has a positive and significant effect on consumer satisfaction (3) Product quality has a positive and significant effect on purchasing decisions (4) Price has a positive and significant effect on purchasing decisions (5) Consumer satisfaction has a positive and significant effect on purchasing decisions (6) Consumer satisfaction is able to relate positively and significantly between product quality and purchasing decisions (7) Consumer satisfaction is able to relate positively and significantly between price and purchasing decisions.